Perempuan dalam Gengaman Ekonomi Politik Kapitaliseme - Moh Nutfa; Magfirah T Lapoami; Siska T Alingkas (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract This paper aims to explore the problem of the body and image of women trapped in the iron framework of capitalism through the industrial political economy system of capitalism laden with patriarchal constructions. Through this paper, it is hoped that there will be reflection and ideological awareness of women for the movement for change. The research approach used is the postmodern approach. The problem is analyzed using the perspective of Michel Foucaut's knowledge and power as well as the perspective of Jean Baudrillard's simulakra. The results of the analysis found that the capitalist political economy system through industrialization has trapped the body and image of women into contemporary culture, making it difficult to escape the grasp of the construction culture of patriarchal capitalism. It concludes that women's bodies, images and even sexuality are cultural constructs of capitalism that continue to position women on endless subordination.